Model Pembelajaran Kooperatif Team Games Tournament dalam Pembelajaran Mahārah Kitābah di Perguruan Tinggi - Naseha, Siti Durotun (Aphorisme: Journal of Arabic Language, Literature, and Education, 2022)
The study aims to describe TGT (Team Games Tournament) cooperative learning model as an alternative learning strategy to increase student motivation and creativity in various aspects of language skills, including Arabic. This research method uses qualitative and quantitative research. The subjects in this study were students majoring in Madrasah Ibtidaiyah Teacher Education at STAI Al-HIKAM Malang. Data collection techniques in this study were obtained through observation, interviews, and documentation. The research instrument used the implementation observation sheet. The results of this study are: a) Based on the presence and recap of the student learning outcomes score sheet. b) Based on the structured interview sheet the implementation of the students after using the TGT (Team Games Tournament) cooperative learning model for Arabic language learning. The study results indicate that learning using the TGT (Team Games Tournament) learning model can improve Arabic learning abilities by making students more active and enthusiastic in the learning process.